2011
DOI: 10.1002/em.20588
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of excess tryptophan metabolites in cancer

Abstract: Tryptophan is metabolized through serotonin, indole, and kynurenine (KN) pathways. Uptake of an excess amount of tryptophan accompanied with vitamin B6 deficiency may result in the accumulation of higher concentrations of metabolites mainly from the KN pathways in the bladder. These metabolites could interact with nitrite to become mutagenic nitrosamines. They could be a promoter in the initiator-promoter model of carcinogenesis. They produced bladder cancer when implanted in the bladder. They also interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 152 publications
(150 reference statements)
1
54
0
1
Order By: Relevance
“…While in transplantable models both treatments were alone sufficient to delay tumor growth, in the TRAMP model, neither 1-MT nor anti-CD25 antibodies or their combination impacted on disease progression and T-cell tolerance associated with tumor growth [82]. All together, our data [82] and those reported by Kallberg et al [151] suggest that IDO has a more relevant direct effect on tumor cells [152], which is not fully inhibited by 1-MT. IDO induces expression of a novel tryptophan transporter in mouse and human tumor cells that is responsible for 50% of the tryptophan uptake [153].…”
Section: Catabolism Of Tryptophan: Indoleamine 23-dioxygenasesupporting
confidence: 65%
“…While in transplantable models both treatments were alone sufficient to delay tumor growth, in the TRAMP model, neither 1-MT nor anti-CD25 antibodies or their combination impacted on disease progression and T-cell tolerance associated with tumor growth [82]. All together, our data [82] and those reported by Kallberg et al [151] suggest that IDO has a more relevant direct effect on tumor cells [152], which is not fully inhibited by 1-MT. IDO induces expression of a novel tryptophan transporter in mouse and human tumor cells that is responsible for 50% of the tryptophan uptake [153].…”
Section: Catabolism Of Tryptophan: Indoleamine 23-dioxygenasesupporting
confidence: 65%
“…[59][60][61] It has been reported that the decreasing energy metabolism in the human body under various pathological conditions disturbs the metabolic pathways of the urea cycle resulting in the altered concentrations of urea and creatinine excretion in urine. [48] Creatinine end product of muscle metabolism is filtered by the kidneys from the blood and excreted in urine. [43] From Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because tryptophan metabolism is related with the immune response of the human body, any alterations in the tryptophan metabolism and the rate-limiting enzyme indoleamine 2,3-dioxygenase activity may lead to changes in the physiopathological conditions and act as a promoter in the progression of cancer and other disorders such as neuropsychiatric syndromes and other depressive disorder. [48,70,71] Earlier literature reports that indole -a metabolic intermediate of tryptophan -is an intoxicating co-carcinogen for the urinary bladder cancer in animal models. It is formed from the dietary tryptophan by tryptophanase of intestinal micro flora such as Escherichia coli.…”
Section: Discussionmentioning
confidence: 99%
“…These genotoxic substances include a variety of Copyright: Copyright©2012 Deepa P.V., et al This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution and reproduction in any medium, provided the original author and source are credited. chemical compounds [2]. In the living cell, DNA undergoes frequent chemical change, especially when it is replicated.…”
Section: Introductionmentioning
confidence: 99%
“…Mutagens are chemicals or physical factors (such as radiation) that increase the rate of mutation in the cells of bacteria, plants and animals (including humans) [3]. Chemicals able to induce genotoxic effects by mechanisms other than covalent binding are of special interest to scientist [2]. A great deal of work is being devoted to the validation of genotoxicity test procedures able to detect drugs that cause genetic damage by interaction with other cellular targets such as enzymes and microtubules particularly because they play a critical role in DNA replication or in the segregation of chromosomes during cell division [4].…”
Section: Introductionmentioning
confidence: 99%